A Home Gardening Guidance System - Balakrishnan, Krisnaa; Mohd Yunus, Mohd Amin (Applied Information Technology And Computer Science, 2022)
Home gardening defines the cultivation of flowers, fruits, vegetables, or ornamental plants for the personal use of the owner of a lot. However, not many people have green fingers or know gardening. Hence, if they proceed with the gardening, they might fail to grow a plant. Therefore, Home Gardening Guidance Mobile Application was created to guide the community in gardening practices and learn more information related to gardening. The object-oriented approach was chosen to design the system. The software used to develop the proposed application is Unity Hub. C# programming is used as a programming language to develop the proposed application. This application is expected to help the community people who are new or lack knowledge regarding home gardening to conduct gardening all by themselves by providing videos related to gardening, requirements of plants, and significant dates for each plant. Moreover, this mobile application supports the people in the community to eat healthy by growing their vegetables in their garden.